Um sistema de reputação para interação baseada em serviços - Molina, Fernando Henrique Ferrarezi (Universidade Federal de São Carlos, 2016)
Service-based communication is becoming increasingly relevant, as seen in the Internet of Things scenarios. Choosing an adequate service however can be a difficult task, as this form of communication may involve sensible resources and data. A trustworthy, safe, and privacy preserving mechanism is desirable for service selection. Reputation systems can help in this selection. This thesis presents a reputation system for service selection based on the security and privacy mechanisms of crypto-coins. In order to evaluate the performance of the proposed mechanism in the identification of low quality service providers we also investigated the use of different formulations used to determine a reputation based on peer voting. Results from simulation show the proposed system architecture is viable and supports large adoption via a scalable infrastructure. The performance analysis of different formulations for the calculus of reputations also shows that the recent behavior of an entity is the most impacting factor in establishing its reputation.
Keywords: D2D; Internet das coisas; Sistemas de reputação; Comunicação baseada em serviços; P2P; Internet of things; Reputation system; Service-based communication; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO